Changes in fire activity and biodiversity in a Northeast Brazilian Cerrado over the last 800 years. (December 2022) - Xavier, Sergio Augusto Santos; de Araújo, Francisca Soares; Ledru, Marie Pierre
Abstract: Understanding vegetation dynamics is essential to interpret long-term ecological changes under different precipitation regimes and land use scenarios. Northeastern Brazil has been subjected to both climatic and anthropic disturbances in recent centuries. This paper presents a high-resolution record from the SAC18 sediment core, collected in a Cerrado ecotone in the Sete Cidades National Park. Multiproxy analyses based on pollen, charcoal and grain size showed the Cerrado landscape was restructured during dry and wet intervals over a period of 800 years. The beginning of the record was marked by a dry episode, testified by the presence of a drought resistant taxon Curatella (wild cashew tree) and coincided with the Medieval Climate Anomaly (950–1250 CE). Almost no fire activity was observed between 1210 and 1300 CE, linked to reduced human presence during this dry period. A wetter interval began in 1400 CE, with expansion of the palm swamp and the moisture-related tree/herbaceous taxa Myrtaceae and Spathiphyllum, which was synchronous with the Little Ice Age (1400–1700 CE). Reduced burning of biomass and the absence of deforestation at the beginning of the wet interval changed to extensive fires and deforestation after 1650 CE, enabling dating of the arrival of European colonists in the north of Piauí State. Fires stopped after the creation of Sete Cidades National Park in 1961 CE, resulting in the expansion of the Cerrado arboreal cover. This study provides new knowledge about past human occupation of the Northeastern Cerrado, defined by three types of land use practices (indigenous, colonist and protection policy), and underlines the importance of including historical aspects of the landscape in future conservation scenarios. Highlights: Effects of climatic and human disturbances in north-eastern Brazil. Changes in fire activity and vegetation linked to different land-use phases. Sediment cores can reconstruct recent perturbations of the landscape. Integral protection reserves can reverse centuries of anthropogenic disturbance.